1990
DOI: 10.1038/ki.1990.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low molecular weight proteins and dextran on renal cathepsin B and L activity

Abstract: Renal extraction of low molecular weight proteins (LMWP) accounts for 30% to 80% of their total metabolic clearance. Extraction includes glomerular filtration, proximal tubular uptake, and intralysosomal proteolysis. To characterize the anatomic sites and enzymes involved in digestion of reabsorbed LMWP, the lysosomal proteases, cathepsin B and L, were measured by ultramicroassay in isolated S1, S2 and S3 segments of the proximal tubule of proteinuric rats. Increased glomerular filtration and tubular uptake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Rhabdomyolysis has been shown to associate with accumulation of myoglobin in lysosomes and its accumulation has proved to be remarkably reduced in megalin-deficient mice [6]. In addition, data show that injections of low-molecular weight proteins (myoglobin and lysozyme) increase the activity of the lysosomal proteases, cathepsins B and L in rats' proximal tubules thus promoting intralysosomal degradation of myoglobin [7].…”
Section: A N U S C R I P Tmentioning
confidence: 97%
See 2 more Smart Citations
“…Rhabdomyolysis has been shown to associate with accumulation of myoglobin in lysosomes and its accumulation has proved to be remarkably reduced in megalin-deficient mice [6]. In addition, data show that injections of low-molecular weight proteins (myoglobin and lysozyme) increase the activity of the lysosomal proteases, cathepsins B and L in rats' proximal tubules thus promoting intralysosomal degradation of myoglobin [7].…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…1). Obviously, after entering renal tubule cells, most likely by endosomes, myoglobin is transported into lysosomes with subsequent cleavage by lysosomal enzymes [7]. This hypothesis is underscored by the fact that a large amount of myoglobin is detected in kidneys only on the first day after rhabdomyolysis and later immune staining cannot reveal myoglobin [4].…”
Section: Myoglobin Absorption By Renal Tubule Cells and Its Degradationmentioning
confidence: 98%
See 1 more Smart Citation
“…The precise mechanism, whether due to free iron, heme, or heme protein, and which free radical mechanism is involved, as well as which cellular organelles are affected, are still debated (11,26). It has been convincingly shown that myoglobin undergoes reabsorption from the glomerular filtrate and is catabolized within proximal tubule cells (2,14,21). Thus it is conceivable that particular components of myoglobin can act on different intracellular levels with the involvement of diverse radical species during reabsorption of holoprotein and its subsequent decomposition.…”
mentioning
confidence: 99%
“…Electron microscopic analyses of proteinuric kidneys reveal fully loaded lysosomes, cytoplasmic protein droplets, and/or crystalline protein inclusions, indicating that the capacity of the lysosomal digestive function has been substantially exceeded [1]. In proteinuric rats, cathepsin B and L synthesis rates increase, possibly as an adoptive mechanism, which may in part compromise the overloaded state [78]. It is possible, however, that such activation may have an adverse effect due to uncontrolled digestion of molecules important for cell phenotype and homeostasis.…”
Section: Overload Proteinuriamentioning
confidence: 99%